Coaching e aconselhamento pastoral: um diálogo possível? - Queiroz, Silvia Helena Barreto Silva (2015)
Disrupted family relations, new family profiles, challenges posed by work and studies and various social vulnerabilities have made people seek professional or spiritual support. Pastors, priests and other religious leaders have been increasingly summoned to understand human behavior and to know how to advise in face of conflict and adversities inherent to life in society. This research presents a qualitative study on the possibility of employment of Coaching in tending to and accompanying people in pastoral and parish offices. Coaching is a form of individual or collective accompaniment of people guiding them towards effective achievement of life objectives and goals. Widespread in professional circles, Coaching is still little known/employed in religious context. This is a bibliographic research proposing the interaction of Pastoral Counseling and Coaching. It discusses the activity of Pastoral Counseling, from its conceptualization and origins to its applicability with regard to the dilemas encountered in the contemporary world. In parallel, this research outlines considerations on the history of Coaching, its contribution and applications in today's society. The mutual influence of one activity upon the other, as well as future prospects of the interaction of Coaching and Pastoral Counseling is highlighted. The paper concludes that the union of these methodologies of accompanying people may be useful in interventions in contexts of diverse social vulnerabilities. It can, therefore, provide relevant contributions to leaders of Christian churches and faith communities.